Pembaharuan Pendidikan Islam Perspektif Fazlur Rahman Dalam Perguruan Tinggi Agama Islam - Syahri Syahri (Scidac Plus, 2022)
Fazlur Rahman's ideas about renewal of Islamic higher education are closely related to the improvement of Islamic education today. The final conclusions of this paper are (1) the thought formulation of the concept of thinking about Islamic higher education that will be developed must be built on a solid spiritual paradigm, intellectually superior, and gracefully moral according to the Qur'an as the first and foremost reference. (2) a curriculum that is open to the study of philosophy and social sciences. (3) If Islamic universities in Indonesia are willing to follow FazlurRahman's educational thinking, then the desire of Indonesian Muslims to develop knowledge will be stronger, the dichotomy of science will be increasingly eroded.